Panduan Alih Media Karya Tugas Akhir Teknik Mesin Menggunakan Aplikasi Nitro Pro 8 - Putra, Teguh Maha; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractTransfer of media to digital format is an alternative choice to preserve the information content of library materials, because this format can be stored on relatively large capacity and durable storage media. In making this Media Transfer guide the Nitro Pro 8 application is used. The reason is that it is easier in the process of transferring information from word to pdf, as well as the availability of various menu options used to support the transfer process. Nitro Pro 8 itself is a software that we can use to read, create, edit and share PDF files. Nitro Pro allows us to process the batch file to convert documents to pdf. Nitro Pro is often called Nitro Pro PDF, which means a very good software for handling PDF files.Keywords: transfer, digital, Nitro Pro 8, libraryÂ